Packaging, Persuasion, Caregiver and the Child Consumer: A Content and Discourse Analysis of Nice & Natural’s ‘Fruit Blocks’ and ‘Fruit Unicorns & Friends’ - Bokkasam, Guru Naga Goutam (Auckland University of Technology, 2026)
This research examines the persuasive power of child-targeted food packaging within the contemporary marketing environment of Aotearoa, New Zealand, focusing on how visual and linguistic strategies construct meaning for both children and caregivers. Positioning packaging as a key discursive and semiotic site, the study analyses two products from Nice & Natural’s fruit-based snack range - ‘Fruit Blocks’ and ‘Fruit Unicorns & Friends’ - through a qualitative approach integrating content and discourse analysis. Drawing on Neuendorf’s seven-step framework and Dryzek’s four-part model, the findings show that packaging operates as a dual-audience communication tool: it engages children through fantasy-driven elements such as bold colours and playful characters, while simultaneously reassuring caregivers through a 'health-halo' effect created by claims like 'contains real-fruit juice', 'no artificial colours or flavours', and 'gluten free'. These strategies position processed snacks as responsible dietary choices. The study argues that packaging functions as a persistent marketing force that operates beyond the reach of New Zealand’s voluntary advertising codes, exposing a regulatory gap that enables brands to shape children’s perceptions while appealing to parental concerns about nutrition. It calls for stronger regulation of child-targeted packaging and increased media literacy to better protect young consumers, contributing to broader debates on ethical branding at the intersection of communication, marketing, and public health.